Identifying privacy concerns on the formation of courtyards - Nejadriahi, Halleh; Dinçyürek, Özgür (Open House International Association P.O. Box 74, Gateshead, Tyne and Wear, 2015)
Rapid changes due to the globalization process, cause in disappearance of traditional values and identity in the new architectural designs, particularly in the historical settlements. Presence of courtyard in the houses of Middle Eastern and Mediterranean countries dates back to nearly six thousand years ago.Privacy is one of the fundamental notions in the spatial organization of the traditional houses in this region and courtyard is the main component that assists achieving privacy in such houses. Kashan as one of the ancient cities of Iran possessing a considerable number of distinctive traditional courtyard houses, is crucial to be interrogated in terms of its traditional architecture to maintain its values and to sustain identity of the city. Space syntax as an effective method to clarify the spatial pattern of buildings and the degree of privacy in the interior spaces is applied in this study to identify privacy concerns on the formation of courtyards in the spatial organization of the traditional houses of Kashan. This paper may contribute in providing an approach for distribution of spaces in the house according to their level of privacy and its relationship in the process of current house layout design.
Keywords: Courtyard; Kasha; Privacy; Space syntax; Traditional houses